Analisis Perhitungan Harga Pokok Produksi Sebagai Dasar Penetuan Harga Jual Kopi Bubuk (Studi Kasus UD. Cipta Karya Sari, Desa Unggahan, Kecamatan Seririt) : (Studi Kasus UD. Cipta Karya Sari, Desa Unggahan, Kecamatan Seririt) - Wulandari, Purwani Laksmi; Diatmika, I Putu Gede; Wiguna, I Gd Nandra Hary (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze the calculation of the cost of production (CoP) as the basis for determining the selling price at UD. Cipta Karya Sari, a ground coffee business located in Unggahan Village, Seririt District. The main issue identified is that the company's CoP calculation does not fully account for all cost components, particularly fixed overhead costs, resulting in an inaccurate selling price determination. This research employs a descriptive quantitative method. Data were collected through observation, interviews, and documentation, and analyzed using the full costing method. The findings reveal that the CoP calculation used by UD. Cipta Karya Sari includes only direct costs such as raw materials, labor, electricity, and gas. When compared to the full costing method, there is a cost difference of IDR 1,165. This discrepancy further results in a selling price difference of IDR 1,280.